Historical and Contemporary Psychoanalytic and Bioenergetic Perspectives of Sexuality: Lets Bring it Back into the Therapy Room - Resneck-Sannes, Helen (Bioenergetic Analysis, 2018)
In the late 60s and 70s sexuality occupied center stage in psychoanalysis and then retreated as a focus of inquiry. The increase of claims against therapists for sexual violations, as well as the emergence of more relational analytic therapies, contributed to the avoidance of addressing sexuality in the therapy room. During this time, the psychoanalytic definition of «normal” sexuality was evolving, as well as our notions of gender. Reichian psychotherapy, and its offshoot Bioenergetic Analysis have always seen sexuality as integral to the healthy functioning of the individual. This paper translates current psychoanalytic concepts of healthy sexuality into its somatic counterparts in bioenergetic theory. A case is presented illustrating how these concepts manifest in practice. Exploring sexual fantasies and clients’ preferences for certain types of pornography is viewed as helpful for understanding the dynamics of parenting, and for clarifying transferential and countertransferential issues.